Effect of Delayed Diagnosis of Phenylketonuria With Imaging Findings of Bilateral Diffuse Symmetric White Matter Lesions: A Case Report and Literature Review - Chen, Shuna; Zhu, Mingqin; Hao, Yulei; Feng, Jiachun; Zhang, Ying (Frontiers in Neurology, 2019)
Phenylketonuria is a hereditary metabolic disorder due to the deficiency of tetrahydrobiopterin or phenylalanine hydroxylase. Delayed diagnoses of it manifest a progressive irreversible neurological impairment in the early years of the disease. Guthrie test and tandem mass spectrometry aided in early detection and intervention of phenylketonuria which significantly decreased the disability of patients as well as reducing the need for diagnosis in adult. This is a case report of a 60-year-old Asian man, characterized by severe visual-spatial disorders and bilateral diffuse symmetric white matter lesions on magnetic resonance imaging, was diagnosed as phenylketonuria with his congenital mental retardation sibling. Heterozygous mutations exist in gene encoding PAH c.1068C>A and c.740G>T. During the diagnosis, we looked up at other late-onset genetic diseases considered to occur rarely but gradually revealed a similar clinical manifestations and significant white matter lesions gaining importance in guiding to correct diagnosis and treatment. So we made a comprehensive review of phenylketonuria and other inherited diseases with major prevalence in adulthood with prominent white matter involvement. Our study aims to help neurologists to improve recognition of metabolism-related leukoencephalopathies without neglect of the role of congenital genetic factors.